The outstanding beneficial roles of irisin disorders. - Ilcın, Saadet; Algül, Sermın; Ozcelık, Oguz (My University, 2022)
Depression is a widely observed psychiatric disorder that affects a quite large number of people all around the world. A major depressive disorder (MDD) is a multifactorial disease that IS associated with fluctuations in appetite, body weight, and energy situations in addition to serious mood problems. The aim of this review is to investigate a possible link between energy regulatory hormones of irisin and depressive disorders. Irisin is a hormone that plays a significant role in the regulation of lipid and glucose metabolism in skeletal muscle and adipose tissue. Irisin was also reported to play significant roles in the central nervous system. In the literature there are reports indicating a beneficial antidepressant role of irisin in MDD. It should be emphasised that the antidepressive effects of exercise could be the result of exercise-induced increased hormones of irisin.
Keywords: Depressive Disorder, Major; Adipose Tissue; Humans; Muscle, Skeletal; Exercise; Fibronectins; 3. Good health